Modulation of Trichromatic Emission Centers in Organic–Inorganic Hybrids for Optoelectronic Applications - Cai, Weidong; Li, Chongyuan; Guo, Qiang; Ji, Fuxiang; Zhang, Muyi; Zhan, Yiqiang (Nano-Micro Letters, 2026)
Organic–inorganic metal halides (OIMHs) have emerged as highly promising novel multifunctional optoelectronic materials, owing to their easily adjustable properties from a variety of combinations of different components. But it is still difficult and rare to realize highly tunable multicolor luminescence within the same material. In this work, we successfully incorporated three adjustable emission centers in OIMHs to synthesize a novel OIMH (NEA)2MnBr4, with each emission center capable of emitting one of the primary colors—red, green, and blue. The green and red emissions originate from the tetrahedron and octahedron structures in the Mn-based frame, while the blue can be attributed to the contribution of organic components. Additionally, to achieve comparable emission intensity among the three primary colors, we enhanced the blue emission performance by optimizing the ratio of organic structure components and incorporating chirality in the OIMHs. The resulting high-quality films can be obtained by spin-coating method with a photoluminescence quantum yields of up to 96%. More interestingly, by the dual manipulation of excitation wavelength and temperature, the sample can be emitted at least seven distinct colors including a standard white luminescence at (0.33, 0.33), opening up promising prospects for multicolor luminescence applications such as high-end anti-counterfeiting technology, light-emitting diodes, X-ray imaging, latent fingerprints, humidity detection, and so on. Therefore, based on application scenarios and requirements, our research on this highly tunable luminescent OIMH material lays a solid foundation for further development of various functional properties of related materials. Highlights: 1 A novel chiral (NEA)₂MnBr₄ was obtained by introducing three independently tunable primary-color emissive centers. 2 Comparable emission intensities among the three primary colors were achieved by optimizing components and introducing chirality. 3 By means of dual control of excitation photon energy and temperature, the sample can emit at least seven different colors, including standard white light emission at (0.33, 0.33).